Enhancing Student Engagement With Indonesian Sharia Banking: The Role Of Sharia Financial Literacy - Amrin (Jeksyah: Islamic Economics Journal, 2023)
The purpose of this study was to find out and analyze the influence of the level of Islamic financial literacy on the interest in using Bank Syariah Indonesia products. This study uses quantitative research with associative types. The data collection technique uses a questionnaire with a population of all Islamic banking students class of 2021, Faculty of Economics and Islamic Business, UIN Syarif Hidayatullah Jakarta. The sampling technique used purposive sampling with the criteria of students who did not have accounts at Islamic banks, namely as many as 67 people. The analysis technique used is simple regression analysis with the help of SPSS version 20 software. The results showed that first, Islamic financial literacy level has a positive and significant effect on students' interest in using Islamic bank products with a tcount of 7.964 (> 1.99714) and a significance value of 0.000 (<0.05).The coefficient of determination (R2) is 0.494 which means that the ability of Islamic financial literacy to explain students' interest in using Islamic bank products is 49.4%. Second, the better the Islamic financial literacy level of a student, the higher the interest in using products at Islamic banks. Thus, Islamic financial literacy is needed with high intensity so that it provides benefits for students and the wider community.